COMMON MISTAKES DONE BY THE STUDENTS OF 6TH SEMESTER IN USING ENGLISH IN THE PRACTICE OF RESTAURANT'S SEQUENCE OF SERVICE ORDER - Jokosaharjo, Sulistyoadi; Subadra, I Nengah; Hendra, I Ketut Yos (Jurnal Manajemen Pelayanan Hotel, 2019)
English mastery plays an important role in tourism and hospitality industries in Bali. STIPAR Triatma Jaya as one of tourism colleges in Bali has to prepare the students with sufficient English skill. To improve their English skill, this research tries to find out some weaknesses in using English in the practice of restaurant's sequence of service order. The mistakes done by the students were derived from 4 types of sentence (Murar, 2011). The results show that there are 24 types of mistake, in which, the most common ones are the use of be and article. Keywords : English mastery, types of sentence, restaurant's sequence of service order.